Binary PCL-waste photopolymer blends for biodegradable food packaging applications - Gurler, Nedim; Pekdemir, Mustafa Ersin; Torgut, Gulben; Kok, Mediha (Elsevier, 2023)
The aim of this study is to prepare waste photopolymer (WPP) / poly e-caprolactone (PCL) blends that can be used in food packaging with different ratios (5%, 10%, 20% and 30%) WPP. The structural properties of the blend films were characterized by attenuated total reflection-fourier transform infrared spectroscopy (ATR-FTIR), thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC). Opacity, surface color, water vapor permeability and shape memory properties of these films were examined. Pure PCL film exhibited more thermal stability compared to PCL/WPP blend films. Therewithal, the glass transition temperature of the pure PCL film showed a shift. Water vapor permeability improved with the addition of WPP. L*, a* and transmittance values reduced with increasing WPP, but b * value increased. It was thought that these polymer blends would enable to be used as packaging material in terms of compatibility and waste evaluation.
Keywords: Waste photopolymer; PCL; Food packaging; Shape memory; Thermal